Pemberdayaan Sosial Perspektif Hadis (Analisis Hermeneutika Hadis Kontekstual) - Abdul Malik; Muhammadiyah Amin; La Ode, La Ode Ismail Ahmad (AL-MUTSLA, 2025)
"Understanding the Prophet’s hadith is not only about textual transmission, but also about the practice and spirit of the teachings. The Prophet’s hadith always contain important messages that are inseparable from the Prophet’s presence and position as the Messenger of the Ummah. However, today, the Prophet’s hadith seems to be practiced only in formal settings, such as the Prophet’s dress, use of the siwak, and so on. In fact, the Prophet’s hadith contain a strong moral message, concern, and agenda for social change. This article poses three questions: what is the concept of social empowerment contained in the hadith? What is the historical context of the hadith regarding social empowerment? And how can we contextualize the hadith regarding social empowerment?. This article uses a hermeneutical analysis of hadith, exploring the meaning of social empowerment in the hadith and its relevance to today’s context. Using this analytical method, several findings emerge: (a) Matan أَيُّ الْكَسْبِ أَطْيَبُ؟ قَالَ: ‌عَمَلُ ‌الرَّجُلِ gives the message that humans need to rely on their potential in working and improving their lives. The wording of the hadith اذْهَبْ فَاحْتَطِبْ gives the message that humans need to eliminate the inlander mentality, begging and throwing away social prestige; (b) the hadith has a historical context of Arab reality in the form of social classes giving birth to a society with a marginal, low mentality, loss of life spirit and the proliferation of the inlander mentality and begging. (c) The contextual meaning of the hadith regarding social empowerment is relevant to today’s conditions, where the phrase "’Amal Rajul Biyadihi’" can be interpreted as doing anything, whether manual labor or soft work (office work), to meet the necessities of life. Another message is that a weak mentality and the Fear of Missing Out (FOMO) are important to eliminate. Humans must be close to social reality and grow stronger from the social issues they face.